Effect of occult malignancy on femoropopliteal bypass graft thrombosis - Png, C Y Maximilian; Wang, Linda J; DeCarlo, Charles S; Latz, Christopher A; Sumpio, Brandon J; Weinberg, Ido; Eagleton, Matthew J; Dua, Anahita (Journal of vascular surgery, 2021)
The presence of cancer increases arterial thromboembolic events, specifically myocardial infarction and stroke, before a formal diagnosis of cancer. To the best of our knowledge, this increase in thrombotic risk has not been studied in patients with lower extremity bypass grafts. In the present study, we aimed to determine the effect of occult cancer on femoropopliteal bypass patency. A retrospective review of femoropopliteal bypass procedures completed from 2001 to 2018 was performed. International Classification of Diseases, 9th and 10th revision, codes corresponding to breast, lung, prostate, colorectal, skin, brain, and hematologic cancer were used to identify patients who had had occult cancer. Occult cancer was defined as cancer diagnosed within ≤1 year after the bypass procedure. The demographics, comorbidities, bypass configuration and conduit, 1-month, 3-month, 6-month, and 1-year occlusion rates, major adverse limb events, and mortality rates were analyzed. Statistical analysis included t tests, χ tests, and Cox regression analysis. A total of 621 procedures in 517 patients met the inclusion criteria. Of the 621 procedures, 36 (5.8%) were classified as procedures in patients with occult cancer. The patients with occult cancer had had higher occlusion rates at 3 months (27.8% vs 8.0%; P < .001), 6 months (30.5% vs 15.1%; P < .01), and 1 year (44.4% vs 19.8%; P < .001). In Cox regression analysis for bypass thrombosis at 1 year, the only significant predictors were occult cancer (hazard ratio [HR], 2.03; P = .01), below-the-knee distal target (HR, 1.88; P < .01), and a compromised conduit (HR, 2.14; P < .001). We found an increase in bypass graft thrombosis rates in patients who had undergone femoropopliteal bypass who had had occult cancer. Thrombosis of the graft within 1 year postoperatively might be a sign of occult cancer.